Slovenski emigranti na začetku devetdesetih let - regionalna analiza - Bevc, Milena (Dve domovini, 1995)
The paper deals with the empirical analysis of those Slovene emigrants who still have permanent residence in Slovenia. The main source of data are the last two censuses of population combined with the data of the Bureau of Employment of the Republic of Slovenia.Two aspects of emigration are analyzed: 1.the stock of emigrants at the time of the last two censuses, 2.the flow (outflow and reverse flow) during the period 1981-1991. Both aspects are analyzed firstly for all the emigrants and secondly for the highly educated emigrants. The regional dimension is also included since there are great differences in the mentioned aspects of emigration among regions. The paper confirms the common knowledge that during the 80s and in the beginning of the 90s the brain drain was the reality in Slovenia, especially in some most problematic regions.
Keywords: 1981-1991; ekonomske migracije; emigracija; Slovenci; Slovenes; slovenski izseljenci